2019
DOI: 10.1016/j.neuroimage.2019.03.062
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based approach to improve decoded neurofeedback performance

Abstract: The neural correlates of specific brain functions such as visual orientation tuning and individual finger movements can be revealed using multivoxel pattern analysis (MVPA) of fMRI data.Neurofeedback based on these distributed patterns of brain activity presents a unique ability for precise neuromodulation.Recent applications of this technique, known as decoded neurofeedback, have manipulated fear conditioning, visual perception, confidence judgements and facial preference. However, there has yet to be an empi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Hyperalignment achieves this by taking advantage of shared high-dimensional patterns in representational content between subjects. Another study showed that offline simulations can be used to estimate optimal parameters for experiment timing and real-time fMRI preprocessing, which can lead to greater decoding accuracy and neurofeedback performance (Oblak, Sulzer, and Lewis-Peacock 2019) . Similar approaches should be applied going forward to optimize the efficacy of DecNef tasks, thereby giving us greater power to investigate the relationship between confidence and consciousness.…”
Section: The Effect Of Neurofeedback On Color Discriminationmentioning
confidence: 99%
“…Hyperalignment achieves this by taking advantage of shared high-dimensional patterns in representational content between subjects. Another study showed that offline simulations can be used to estimate optimal parameters for experiment timing and real-time fMRI preprocessing, which can lead to greater decoding accuracy and neurofeedback performance (Oblak, Sulzer, and Lewis-Peacock 2019) . Similar approaches should be applied going forward to optimize the efficacy of DecNef tasks, thereby giving us greater power to investigate the relationship between confidence and consciousness.…”
Section: The Effect Of Neurofeedback On Color Discriminationmentioning
confidence: 99%
“…These results show that while motor 165 repetition may have caused changes in finger behavior, there is no evidence that increasing 166 pattern overlap through neurofeedback was able to increase confusion between fingers in the 167 motor or sensory domains. data was able to predict participants' abilities in a subsequent decoded neurofeedback task 192 10 (Oblak et al, 2019). By examining baseline variability of patterns, future studies may be able to 193 determine the feasibility of controlling specific neural patterns.…”
Section: Differential Modulation Of Finger Preferencementioning
confidence: 97%
“…in terms of visual and semantic processing: [64,65,66]). MVPA methods have been used with success in fMRI neurofeedback studies [60,67,68,69]. 2.…”
Section: Neurofeedback System Componentsmentioning
confidence: 99%